2001
DOI: 10.1023/a:1010580416485
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: A study concerning performance traits of the Ethiopian camel indicated that, in the camel herds examined, there was one active bull camel for 25 females. The bull camel was 5 years old at puberty; it reached rutting vigour at the age of 9 years, the number of mountings per day was 8 during the breeding season, and the reproduction span was 10 years. The female camel reached puberty at 4 years of age; the age at first calving was 5 years, and the lactation period was one year; the calving interval was 2 years, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 5 publications
5
4
0
Order By: Relevance
“…The prevalence of mange mites was higher in female animals, 2.85% than in male animals, 0.64%, So there was a high statistical association of mange mite prevalence with the sex of animals (χ 2 = 5.17, p < 0.05). The present results show the study in agreement with the conclusion of Tefera and Gebreah (2001) , they concluded a highest disease prevalence rate in females gender, Furthermore the behaviour of breeding in males could also be recognized to the transmission of disease to a number of females.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The prevalence of mange mites was higher in female animals, 2.85% than in male animals, 0.64%, So there was a high statistical association of mange mite prevalence with the sex of animals (χ 2 = 5.17, p < 0.05). The present results show the study in agreement with the conclusion of Tefera and Gebreah (2001) , they concluded a highest disease prevalence rate in females gender, Furthermore the behaviour of breeding in males could also be recognized to the transmission of disease to a number of females.…”
Section: Discussionsupporting
confidence: 92%
“…This would be due to the immature immunity of young animals ( Dinka et al, 2010 ). The present study results are in contract with the result of Tefera and Gebreah, 2001 , Dinka et al, 2010 . They concluded that the prevalence was high in young livestock animal than older ones.…”
Section: Discussionsupporting
confidence: 87%
“…The mean age of camels at first calving was 5.84±2.01 years in this study. Table 4 This is in line with the age at first calving noted in previous studies Tefera and Gebreah, 21 for eastern Ethiopia (5 years) and the Afder zone of the Somali region (5.2 years). The mean age of camels at first calving was four years in Somali Regional State Sisay.…”
Section: Age At First Calving and Calving Intervalsupporting
confidence: 90%
“…The Domestic Animal Diversity Information System ( DAD-IS ) database and FAO recognize 97 camel breeds worldwide, based on distribution and specific characteristics ( http://www.fao.org/dad-is/ ). Likewise, in eastern Africa, the classification is generally based on the ethnic groups and geographical distribution of the pastoral communities that own them ( Tefera and Gebreah, 2001 ). The FAO officially recognizes 5 breeds in Ethiopia (Somali/Ogaden, Ethiopian Dromedary, Afar, Anfi, and Borena); however, pastoralists of the region recognize additional breeds ( http://www.fao.org/dad-is/ ).…”
Section: Introductionmentioning
confidence: 99%